Bioactivity and prostate tissue distribution of metformin in a preprostatectomy prostate cancer cohort. Issue 6 (November 2018) - Nguyen, Mike M.; Martinez, Jessica A.; Hsu, Chiu-Hsieh; Sokoloff, Mitchell; Krouse, Robert S.; Gibson, Blake A.; Nagle, Raymond B.; Parnes, Howard L.; Cordova, Catherine; Chow, H-H. Sherry
Abstract : Metformin has recently been shown to have potential to reduce prostate cancer risk. We conducted a randomized, double-blind, placebo-controlled trial to determine the modulating effects of metformin on tissue and systemic biomarkers of drug activity and its distribution into the prostate tissue. Twenty patients with prostate cancer scheduled to undergo prostatectomy were randomly assigned to receive either extended-release metformin or placebo for a median of 34 days before surgery. Prostatectomy and serum samples were analyzed for metformin concentrations, serum biomarkers of drug activity (prostate-specific antigen, insulin, insulin-like growth factor-1, insulin-like growth factor binding protein 3, sex hormone-binding globulin, and testosterone) and tissue biomarkers of proliferation, apoptosis, cell cycle regulation, and mTOR inhibition. For participants in the metformin arm, the prostate tissue and serum metformin concentrations ranged from 0.88 to 51.2 μg/g tissue and from not detectable to 3.6 μg/ml, respectively. There were no differences between the two groups in either the postintervention tissue biomarker expression in the prostatectomy tissue or pre to postintervention changes in serum biomarkers. We conclude that metformin distributes to human prostate tissue, suggesting that metformin could exert its effects directly on tissue targets. However, there was no difference in tissue and systemic drug effect biomarkers between the two treatment arms. Future studies with longer intervention duration and larger sample size should be considered in order to evaluate the potential of metformin for prostate cancer prevention.